Gabrielle Mouton-Kenemuth: capstone - Mouton-Kenemuth, Gabrielle, artist (Colorado State University. Libraries, 2016)
The artist's statement: Throughout the lifetime of every individual there is an evolution of self that takes place. With every new experience we shatter, and undergo a process of reconstruction. Assimilating pieces of our world and drawing from our relationships, we evaluate the newly filled and reflect on the remaining spaces, recombining ourselves into a new whole. My work focuses on this shared human experience of striving to be whole, dealing with the psychological content behind growth, fragmentation, views of self and states of being.
WHOLE
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photography